2021
DOI: 10.3390/molecules26020434
|View full text |Cite
|
Sign up to set email alerts
|

HPLC and ToF‒SIMS Analyses of Toxicodendron vernicifluum Tree Sap Mixed with Other Natural Lacquers

Abstract: Lacquer sap has been used by humans from antiquitywhen it was treated as a luxury item because of its desirable physical properties. In modern times, although access barriers are lower, lacquer is still considered to be rare and valuable. Thus, low quality, inexpensive Vietnamese and Myanmarese lacquers and cashew nutshell liquid are frequently added to the costly Toxicodendron vernicifluum lacquer sap from Korea, China, and Japan. However, these blended lacquers can diminish the quality of artisan works. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Urushiol showed double peaks corresponding to 3-pentadecyl catechol with retention times of 11.29 and 11.77 min, using a 260 nm UV detector. As shown in the previous study, split peaks were observed [25]. The splitting of the peak might originate from the chemical structure of urushiol 15:2, including two double bonds and two phenol groups.…”
Section: Quantitative Analysis Of Lacquer Using Hplcsupporting
confidence: 66%
See 2 more Smart Citations
“…Urushiol showed double peaks corresponding to 3-pentadecyl catechol with retention times of 11.29 and 11.77 min, using a 260 nm UV detector. As shown in the previous study, split peaks were observed [25]. The splitting of the peak might originate from the chemical structure of urushiol 15:2, including two double bonds and two phenol groups.…”
Section: Quantitative Analysis Of Lacquer Using Hplcsupporting
confidence: 66%
“…For thitsiol analysis, acetonitrile and 20 vol.% aqueous acetic acid were mixed at a ratio of 9:1 and analyzed for 40 min using the isocratic elution method and 0.5 mL/min as the flow rate [ 13 ]. For urushiol analysis, acetonitrile and 0.1 vol.% aqueous trifluoroacetic acid were mixed at a ratio of 9:1 and analyzed for 20 min using the isocratic elution method and 1 mL/min as the flow rate [ 25 ]. Detection was performed using a UV detector at 260 nm (for urushiol analysis) and 280 nm (for thitsiol analysis) to obtain chromatograms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-C and C-O-C nature of the cross-links also prohibits wet chemical pretreatments to degrade the lacquer polymer to its monomers, making analysis using state of the art NMR, or chromatographic techniques coupled to mass spectrometry extremely difficult. Even though structural analysis of the cross-linked polymer is problematic, broad identifications can still be obtained using direct surface analysis techniques like Fourier transform infrared spectroscopy (FT-IR) [24,25], time of flight-secondary ion mass spectrometry (ToF-SIMS) [26][27][28] and X-ray photoelectron spectroscopy [29,30]. Those techniques can be utilised to differentiate between the lacquer polymers, but they do not allow us to study oxidative cross-linking or detailed analysis of historical objects decorated with Anacardiaceae lacquer.…”
Section: Introductionmentioning
confidence: 99%